Penyelesaian Metode Quick Simplex Terhadap Metode Dua Fase dengan Dua Elemen secara Simultan pada Kasus Minimum - Elfira Safitri; Sri Basriati; Mohammad Soleh; Ade Novia Rahma (Jurusan Matematika, Fakultas Sains dan Teknologi, UIN Sunan Gunung Djati Bandung, 2021)
Linear programming is a way to solve the problemof allocating limiter resources optimally. One of the methods used in solving the simplex method for mixed constraints is the two-phase method. There is a new approach to solve linear programming problems, namely the quick simplex method is carried out using a matrix to reduce the number of iterations needed to achieve the optimal solution. Completion step for the minimum case are the same as for the maximum case, the difference is only taking the entering variable, namely taking a positive value on the zj-cj line minimum case. The method used in this research is the two-phase quick simplex method. The purpose this study to find out the optimal solution for solving the quick simplex method in the two-phase method for the minimum case. Based on the research result, the quick simplex metode of entering variables and leaving variables can be taken two elements at simultaneously,resulting in fewer iterations than the usual two-phase method.